소수보호의 의미와 ‘양심에 따른 거부’에 대한 관용 - 이연우(Lee Yeon-Woo) (법학연구, 2024)
2018년 헌법재판소는 ‘양심적 병역거부 사건’에서, 그동안 합헌결정을하여오다 판례를 변경하여 양심적 병역거부자를 위한 대체복무제를 규정하지 않은 병역법 조항에 대하여 헌법불합치 결정을 하였다. 헌법재판소는 이 역사적인 결정에서 “다수결을 기본으로 하는 민주주의 의사결정구조에서 다수와 달리 생각하는 이른바 ‘소수자’들의 소리에 귀를 기울이고 이를 반영하는 것은 관용과 다원성을 핵심으로 하는 민주주의의 참된정신을 실현하는 길”이라고 밝혔다. 이로써, 자유민주주의 국가에서의 ‘소수보호의 의미’가 무엇이며, 민주적 다수와 생각이 다른 소수가 이른바 ‘양심에 따른 거부권’을 주장할 때적용되어야 하는 국가적 관용의 원칙이 어떠한 모습이어야 하는지에 대한 논의의 필요성이 제기된다. 자유민주주의 국가에서 공동체의 정치적 의사결정은 필연적으로 다수결에 의할 수밖에 없으나, 이와 함께 다양성을 추구하고 다수에 의하여결정된 공동체 질서에 대한 소수의 승복을 정당화하기 위해서는 의사결정 과정에서 소수의 참여와 영향력 행사의 가능성이 보장되어야 하며, 이러한 소수의 참여 보장이 곧 소수보호의 전형이자 1차적 소수보호라고할 수 있다. 그런데 이러한 1차적 소수보호를 통하여 형성된 법질서에 대해 다시금생각이 다른 소수의 국민이 이른바 ‘양심에 따른 거부권’을 주장할 경우, 2차적 소수보호의 문제가 대두되는바, 이러한 법질서에 대한 예외의 인정은 민주주의 사회에서의 다양성의 추구에도 불구하고 엄격한 요건 하에서만 헌법적으로 정당화될 수 있다. 즉 예외를 무분별하게 허용하는 것은곧 법질서의 파괴요, 국가와 헌법의 해체를 의미하기 때문이다. 또한 ‘양심에 따른 거부권’은 다른 자유권과 전혀 다른 특수성을 갖는다. 즉 자유권은 원칙적으로 무제한적이므로 기본권 주체가 자신의 자유권 행사에 대하여 헌법적으로 정당화할 필요가 없는 반면, 정당한 법질서에 대한 예외를 주장하는 ‘양심에 따른 거부권’은 원칙적으로 제한적이므로 개인이 국가에 대하여 예외(관용)의 허용을 요구하기 위해서는 이를헌법적으로 정당화하여야 한다. 아울러 일반적인 자유권은 법률로써 자유를 제한하는 반면, 양심에 따른 거부권은 법률로써 예외(관용)를 허용함으로써 기본권의 내용을 형성한다는 점에서 ‘기본권 제한적 법률유보’가 아니라 ‘기본권 형성적 법률유보’의 성격을 갖는다고 할 것이다. 따라서 ‘양심에 따른 거부권’의 특수성에 비추어 볼 때 위헌성 심사기준도 과잉금지원칙이 아닌 별도의 기준이 요구된다. 즉 개인적·주관적인내적 상황을 이유로 국민 누구에게나 적용되는 일반·추상적인 법질서에대하여 거부를 주장하는 소수 국민에 대한 예외(관용)의 허용이 헌법적으로 정당화될 수 있는 요건이 필요하다는 것이다. 이러한 관용의 정당화 요건은 크게 기본권 주체의 ‘주관적 요건’과 국가의 법질서가 감당할 수 있는 범위 내라는 ‘객관적 요건’으로 나누어진다고 할 수 있으며, ‘주관적 요건’으로는 첫째, 양심상의 갈등을 초래하는행위가 기본권 주체의 행위로 귀속될 것을 요건으로 하는 ‘양심상 갈등의자기관련성’이 있어야 하며, 둘째로, 개인의 양심이 아무리 주관적이라고하더라도 양심내용이 헌법의 이념과 원리, 가치들에 부합하여야 한다는‘양심내용의 합헌성’이 요구된다. 마지막 ... In 2018, the Constitutional Court, in the 'Conscientious Objection Case', changed its previous precedent and declared unconstitutional a provision of the Military Service Act that did not provide for alternative service for conscientious objectors. In this historic decision, the Constitutional Court said, “In a democratic decision-making structure based on majority rule, listening to and reflecting the voices of so-called ‘minorities’ who think differently from the majority is the way to realize the true spirit of democracy, which is based on tolerance and pluralism.” This raises the need for a discussion about what “minority protection” means in a liberal democracy and what the principles of state tolerance should look like when a minority that disagrees with the democratic majority asserts a so-called “conscientious objection.” First, in a liberal democracy, the political decision-making of a community is inevitably based on majority rule, but at the same time, in order to justify the pursuit of diversity and the submission of minorities to the community order determined by the majority, the participation and influence of minorities in the decision-making process must be guaranteed, and this guarantee of minority participation is the epitome of minority protection and primary minority protection. When a minority of citizens who disagree with the legal order established through such primary minority protection assert a so-called “right of conscientious objection,” the question of secondary minority protection arises, as the recognition of exceptions to the legal order can only be constitutionally justified under strict requirements, despite the pursuit of diversity in a democratic society. In other words, indiscriminate granting of exceptions would mean the destruction of the legal order and the dissolution of the state and the constitution. The “right of conscientious objection” has a completely different specificity from other liberal rights. That is while liberal rights are unlimited in principle and therefore do not require the subject of the fundamental right to constitutionally justify the exercise of his or her liberal right, the “right of conscientious objection”, which claims an exception to the legitimate order of law, is limited in principle and requires the individual to constitutionally justify his or her request for the state to grant an exception(tolerance). In addition, while the general right to freedom restricts freedom by law, the right of conscientious objection is said to be a ‘fundamental right-forming legal reservation’ rather than a ‘fundamental right-limiting legal reservation’ in that it forms the content of fundamental rights by allowing exceptions (tolerance) by law. Therefore, in light of the specificity of the ‘right of conscientious objection’, a separate test for constitutionality is required other than the principle of proportionality, i.e., a requirement that the granting of an exception(tolerance) to a minority of citizens who claim to reject the general and abstract legal order applicable to all citizens due to personal and subjective internal circumstances can be constitutionally justified. The justification(requirement) for such tolerance can be broadly divided into the ‘subjective requirement’ of the fundamental rights subject and the ‘objective requirement’ that the legal order of the country is within the scope that can be afforded. The ‘subjective requirement’ requires, first, the ‘self- connectedness of the conflict of conscience’, which requires that the act causing the conflict of conscience be attributed to the act of the fundamental rights subject. Second, there is the ‘constitutionality of the content of conscience’, which requires that the content of conscience, no matter how subjective it may be, must conform to the ideology, principles, and values of the Constitution. Third, the ‘urgency of conscience’ m... KCI Citation Count: 0